MANAJEMEN TENAGA PENDIDIK DAN KEPENDIDIKAN - Putra, Joni; Asmendri, Asmendri (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The management of teachers and education personnel is an important part of school activities, starting from teaching and learning activities to administrative activities. Their function cannot be completely eliminated as educators and teachers for their students. Likewise, educational staff (principals, supervisors, librarians, administrative staff) are tasked with carrying out administration, management, guidance, supervision, and technical services to support the educational process in educational units. In connection with fostering the professionalism of education staff and education staff, improving the quality of education at every type and level of education has become a national education commitment. In the national education system, organizations that operate within the system are sub-systems that have human resources that need to be managed properly. Some things that must be considered in preparing Educator and Education management techniques Carry out optimal learning preparations, carry out learning, carry out guidance and guidance to actors or students, conduct an assessment of the activities that have been carried out to determine target achievement, conduct an analysis of the achievement of targets that have been carried out. has been established.